Preparation and evaluation of 3 m open tubular capillary columns with a zwitterionic polymeric porous layer for liquid chromatography. Issue 19 (8th September 2016) - Peng, Li; Zhu, Manman; Zhang, Lingyi; Liu, Haiyan; Zhang, Weibing
Abstract : A 3 m zwitterionic polymeric porous layer open tubular column (3 m × 25 μm id × 375 μm od) with a polymeric porous layer thickness of 4 μm was fabricated by the copolymerization of [2‐(methacryloyloxy)ethyl] dimethyl‐(3‐sulfopropyl) ammonium hydroxide and N, N '‐methylenebis(acrylamide). The effects of the diameter of the capillary, reaction temperature, and polymerization time on the preparation of the open tubular column were investigated. Characterized by scanning electron microscopy, the zwitterionic layer was observed to be rough and throughout the fused‐silica capillary homogenously, which increased the phase ratio. The separation of neutral, basic, and acidic compounds demonstrates the strong hydrophilicity of the poly[2‐(methacryloyloxy)ethyl] dimethyl‐(3‐sulfopropyl) ammonium hydroxide coating. In addition, the poly[2‐(methacryloyloxy) ethyl] dimethyl‐(3‐sulfopropyl) ammonium hydroxide porous layer open tubular column was applied for the analysis of flavonoids from the rootstalk of licorice, revealing the potential in separating complex samples. The relative standard deviation of retention time for run‐to‐run ( n = 5), day‐to‐day ( n = 3), and column‐to‐column ( n = 3) of toluene, N, N ‐dimethylformamide, formamide, and thiourea were below 1.2%, exhibiting good repeatability.